PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA XI (PERSERO) SURABAYA - I Kadek Anggara; Nurleila Jum’ati (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to examine and analyze the effect of organizational culture and work motivation simultaneously on employee performance at PT. Nusantara Plantation XI (Persero) Surabaya. The unit of analysis in this study is the employees at PT. Perkebunan Nusantara XI (Persero) Surabaya with 65 people. Samples were taken using saturated sample technique. Data analysis was performed using statistics with SPSS 26 tools. Based on the results of data analysis using the t test it is known that partially organizational culture and work motivation have a significant influence on employee performance. Meanwhile, based on the results of data analysis using the F test, it is known that simultaneously organizational culture and work motivation have a significant effect on employee performance. Thus, companies are advised to pay attention to the organizational culture and work motivation of employees so that their performance is maintained.